A review of the protective effect of melatonin in pesticide-induced toxicity. (4th May 2017) - Asghari, Mohammad Hossein; Moloudizargari, Milad; Bahadar, Haji; Abdollahi, Mohammad
ABSTRACT: Introduction : Pesticides are among the most important chemicals used in agriculture sector. However, their extensive use has polluted the environment and increased human vulnerability to various chronic diseases. Pesticide exposure causes genetic and epigenetic modifications, endocrine disruption, mitochondrial dysfunction and oxidative stress. Areas covered : This review is based on the literature studies currently reported on pesticide-induced toxicity and the protective role of melatonin. Scientific databases such as PubMed, Scopus and Web of Science were searched using keywords 'pesticide' and 'melatonin' up to January 2016. Full length articles related to animal and human exposure were retrieved. A total number of 181 records were obtained, and after excluding the duplicates, 97 papers were further screened on the basis of relevance to the topic. Expert opinion : Melatonin as a broad-spectrum antioxidant is able to penetrate cellular compartments specifically the mitochondria. It is a potent free radical scavenger with low toxicity and desirable solubility in organic and aqueous phases. We are of the opinion that melatonin is a promising agent in minimizing organ injuries induced by pesticides.